2011
DOI: 10.1044/1059-0889(2011/10-0029)
|View full text |Cite
|
Sign up to set email alerts
|

Communication Connections: Service Learning and American Sign Language

Abstract: The connection between service learning and ASL instruction is advantageous because students gained cultural understanding as well as language skills. This course design could be used at other institutions where a Deaf community is accessible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Similar findings are evident in other studies (e.g. Casey & Murphy, 2008;Amerson, 2010;Reading and Padgett, 2011). Interestingly, Nokes et al (2005) reported conflicting results with students' cultural competence decreasing following SL engagement.…”
Section: )supporting
confidence: 72%
See 3 more Smart Citations
“…Similar findings are evident in other studies (e.g. Casey & Murphy, 2008;Amerson, 2010;Reading and Padgett, 2011). Interestingly, Nokes et al (2005) reported conflicting results with students' cultural competence decreasing following SL engagement.…”
Section: )supporting
confidence: 72%
“…Sample sizes ranged from (n = 3) medical students in one qualitative study (Dharamsi et al, 2010b) to (n = 3450) students from multiple disciplines in a quasi experimental study (Astin & Sax, 1998). Examples of the methodological weaknesses identified included samples from single institutions (Beling, 2004;Bentley & Ellison, 2005;Champagne, 2006;Horacek et al, 2009;Leung et al, 2011;Liang En et al, 2011b;Loewenson and Hunt, 2011) with a variety of potential biases, for example, self-selection bias for students (Ngai, 2009;Green et al, 2011;Reading & Padgett, 2011) possible positive reporting bias (Kearney, 2004;Reynolds, 2005;Brown, 2009;Liang En et al, 2011b;Loewenson & Hunt, 2011) and social desirability bias (Casey and Murphy, 2008;Loewenson & Hunt, 2011). Of the 26 Quasi-experimental studies the majority (n = 20) used some form of self-report measure as did (n = 6) of the mixed method studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Practice, repetition, authentic usefulness, and active engagement create the connections to help individuals learn more than one language. Since ASL serves a distinct culture, DHH, the connections students make in learning ASL will help advance understanding and consideration for a different culture (Reading & Padgett, 2011). Dean, Hubbell, Pitler, and Stone (2012) explained the benefits of physical and non-linguistic comparisons in engaging students' perception and analysis visual representations.…”
Section: Connectingmentioning
confidence: 99%